PENGARUH COMMUNITY RELATIONS MANAJEMEN PT ECCO INDONESIA TERHADAP PEMAHAMAN MASYARAKAT DESA TENGGULUNAN TENTANG PENANGANAN LIMBAH INDUSTRI - Sri Wahyuni; Nur Maghfirah Aesthetika; Poppy Febriana (Kanal: Jurnal Ilmu Komunikasi, 2013)
The study, entitled "The Effect of Community Relations conducted by the management of PT Ecco Indonesia toward Tenggulunan community’s Understanding on Industrial Waste Management" aims to determine the effect of community relations conducted by the management of PT Ecco Indonesia toward the Understanding of people living in the vicinity of the company on industrial waste generated. This quantitative study used a sample of 95 respondents. The research data were then analyzed using simple linear regression analysis. The results show that 1) the community relations was done well enough by the management of PT Ecco Indonesia (67.3%), 2) the public's understanding on industrial waste of PT Ecco Indonesia is also quite good (68.8%), 3) there is an effect of community relations of management of PT Ecco Indonesia toward the understanding of people living in Tenggulunan on industrial waste management, 4) the accepted hypothesis shows that that there is a significant relationship between community relations done by the management of PT Ecco Indonesia with public awareness about waste management industry amounted to 81,5%.